Intra city-size distribution in the Yangtze River Delta Region: Equalization or polarization - Pang, Zehua; Zhao, Xianchao; Wang, Chengxiang (Frontiers in Environmental Science, 2023)
In the context of China’s New Urbanization Strategy, a growing number of cities are beginning to experience significant changes in their intra-city structure and size distribution, but systematic research is still lacking. This paper investigated the intra city-size distribution of 214 cities in China’s Yangtze River Delta Region (YRDR) from 1990 to 2020. The study used the Pareto index to portray the equalization differences in intra city-size distribution, and investigated the heterogeneity of its influencing factors using multiscale geographically weighted regression (MGWR). The results showed that most of the cities in the YRDR had a city-size distribution consistent with a Pareto distribution but still tended to be polarized. Among them, the better-developed large cities and regions were more consistent with the Zipf distribution, as were the county-level cities and prefecture-level cities. In terms of spatio-temporal distribution, the intra city-size distribution showed a spatial agglomeration pattern of “polarization in the west and equalization in the east” and the scope and intensity of cold and hot spots reduced. Regarding driving factors, land, industry, and population were essential influences on the intra city-size distribution. Of these, the natural environment and location were important global influencing factors, and economic and social factors only had a more significant influence in 1990 and 2020. The impact of industry restructuring gradually increased, and the population was a significant influence only in the early years. By exploring the intra city-size distribution, this paper provides a scientific basis for the optimization of town structure and policy formulation in small and medium-sized cities, and some new concerns have been proposed.